Altered Glutathione Redox State in Schizophrenia - Yao, Jeffrey K.; Leonard, Sherry; Reddy, Ravinder (Disease markers, 2006)
Altered antioxidant status has been reported in schizophrenia. The glutathione (GSH) redox system is important for reducing oxidative stress. GSH, a radical scavenger, is converted to oxidized glutathione (GSSG) through glutathione peroxidase (GPx), and converted back to GSH by glutathione reductase (GR). Measurements of GSH, GSSG and its related enzymatic reactions are thus important for evaluating the redox and antioxidant status. In the present study, levels of GSH, GSSG, GPx and GR were assessed in the caudate region of postmortem brains from schizophrenic patients and control subjects (with and without other psychiatric disorders). Significantly lower levels of GSH, GPx, and GR were found in schizophrenic group than in control groups without any psychiatric disorders. Concomitantly, a decreased GSH:GSSG ratio was also found in schizophrenic group. Moreover, both GSSG and GR levels were significantly and inversely correlated to age of schizophrenic patients, but not control subjects. No significant differences were found in any GSH redox measures between control subjects and individuals with other types of psychiatric disorders. There were, however, positive correlations between GSH and GPx, GSH and GR, as well as GPx and GR levels in control subjects without psychiatric disorders. These positive correlations suggest a dynamic state is kept in check during the redox coupling under normal conditions. By contrast, lack of such correlations in schizophrenia point to a disturbance of redox coupling mechanisms in the antioxidant defense system, possibly resulting from a decreased level of GSH as well as age‐related decreases of GSSG and GR activities.